Study on Temporal and Spatial Distribution Characteristics of Rock Burst Micro-seismic Incident in Deep-buried Tunnels Based on Micro-seismic Monitoring - LIN Kaisheng; ZHANG Shuyu; JIAO Yuqi (Renmin Zhujiang)
The maximum buried depth of access tunnel of Shuangjiangkou Hydropower Station is up to 500 m, the maximum ground stress level is up to 38.8 MPa, and the strength-stress ratio is relatively low, so rock burst is easily to occur.In response to the above situation, this paper conducts the stability and rock burst monitoring by the micro-seismic monitoring, and researches & analyzes the temporal and spatial distribution characteristics of rock burst micro-seismic incident of access tunnel in the process of excavation, then identifies and delineates the rock burst areas at the access tunnel and the instability areas at surrounding rock, and carries out the back analysis of stress concentration region of surrounding rock.The result shows that the analysis on temporal and spatial distribution characteristics of rock burst micro-seismic incident in tunnels can well forecast on-site rock burst and provide basis for regulation of on-site construction progress and next construction plan, which can provide a reference for similar projects.